Perancangan Sistem Informasi Penjualan Obat Pembersih Kerak Lantai Berbasis Web pada PT Duta Jaya Fritztama - Amellia Julianty Pratiwi; Hasbi Basith Sukarno; Rini Suwartika Kusumadiarti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to analyze, design and build sales information systems at PT. Duta Jaya Fritztama. The design of this sales information system was developed using the PHP programming language using MySQL as the database. The method used is descriptive qualitative method and the system development used is the Waterfall method and the data collection techniques used are interviews, observation and literature study. The problems that occurred at PT. Duta Jaya Fritztama is in a sales system that has been computerized but is not optimal so that the system is less efficient and takes a long time to record sales. The effort to solve this problem is to create a web-based sales information system to make it easier for users in the process of recording sales, improve service, comfort and make company performance more effective and efficient.